STANDy (Standing Bench) / Ahmad Yusri Abu Bakar - Abu Bakar, Ahmad Yusri (Universiti Teknologi MARA, Kedah, 2018)
STANDy is a Standing bench are purpose to seat for a while for waiting purpose . Beside this standing bench can avoid from vandalism activity because it requires a stand while seating and automatically can avoid from homeless to seating and sleeping in it . It's also has been featured with charging port and has a coffee port for waiting purpose . The design was influence by the existing bench but the design has upgraded into a new type of furniture that purpose for a stand resting so the user wouldn't have to seat just lay their back and rest while waiting This design are purpose on the airport area which is KLIA where the waiting seat are limited and people has to seat anywhere while waiting their flight .The design also has been made for a privacy and has an organic and modern concept that suitable for international places like the airport . This standing bench can create resting place while simultaneously providing . optimal utilization of the floor area . Standing bench is something new around Malaysia , so the it is suitable for market and has a new concept and 4111 trending.